ANALISIS PENGARUH KNOWLEDGE MANAGEMENT SYSTEM TERHADAP DAMPAK KINERJA PENGGUNA - Hadi, Miftahul; Hidayat, Rokhmat Taufiq; Johantri, Bagas (Polytechnic of State Finance STAN, 2025)
This study analyzes the use of Knowledge Management System used in the Ministry of Finance by looking at the factors that influence the performance of its users through the use of variables in the information system success model (Delone and McLean Model). The population of this study were users of Knowledge Management System in the Ministry of Finance units other than the Financial Education and Training Agency. The technique used in collecting samples was incidental sampling through the distribution of online questionnaires by obtaining 91 respondents. Data were analyzed using descriptive statistics and inferential statistics with the Structural Equation Modeling technique using the SMARTPLS 4 application. Five of the six hypotheses stated were accepted at a significance of 0.05 while one hypothesis was accepted at a significance of 0.1. In general, it can be stated that the implementation of Knowledge Management System has been running well because it has a positive impact on user performance. Keywords: KMS State Finance; User Performance; Delone and Mclean